G19(P) Improving blood gas sampling in newborn intensive care. (24th May 2017) - Tanney, K; Masood, Y; Eaton, K; Chadwick, C; Dockery, K; Rajai, A
Abstract : Aims: NICU babies often require frequent blood gases. This unit processes 3000–4000 blood gases monthly. Most are done by heel-prick with glass capillary tubes, with potential for needlestick injury. Some units have switched to a safer plastic tube, despite little evidence confirming reliability of results. Locally there were concerns that plastic tubes were unreliable, or would result in increasing sample failures. In a recent QI project, I endeavoured to review our blood gas practices and facilitate change if appropriate. Methods: Historically, incidents with glass tubes were poorly reported, so I set up 'group reporting' to confirm the scale of any problem. I distributed a questionnaire to regional trainees and nurses, seeking feedback on neighbouring experiences. Reassured by positive feedback, we carried out an adult study comparing glass and plastic tube gases at 0, 5, 10, 15, 20 and 30 min postsampling. As a multi-disciplinary team, we then began begin looking closely at our own practices and results. Results: Over four months, twenty glass tubes 'snapped'. Once, this resulted in needle-stick injury and viral screening for operator and baby. 63 people responded to our questionnaire, with 46% using plastic capillary tubes – all satisfactorily. Many reported safety concerns with glass tubes. In adults, no significant differences were seen between 36 corresponding glass and plastic tube gases. One plastic sample failed. As these results were not readily transferrable to our neonatal population, it was decided that a NICU study should be completed for more reassurance. Incidentally we discovered high blood gas failure rates of 30%– 40%, accumulating significant financial loss (£4 per sample), and resulting in repeated heel-pricking. We began to work on improving this significant failure rate. Conclusions: Having obtained ethical approval to carry out a NICU study, I am comparing 105 matched glass and plastic capillary tube gases in neonates, with statistician input for agreement analysis. This trial is ongoing. We have successfully concentrated efforts on education, improving high blood gas failure rates with Focus Weeks, posters, video production, and targeted training for individual operators. Regardless of trial outcome, this project will have enhanced the quality of care we provide for our babies, with safety and infection control implications, and incidental financial benefits.